2016
DOI: 10.1113/jp271473
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic decay of the Ca transient results from increased sarcoplasmic reticulum Ca leak

Abstract: Key pointsr Ca leak from the sarcoplasmic reticulum through the ryanodine receptor (RyR) reduces the amplitude of the Ca transient and slows its rate of decay.r In the presence of β-adrenergic stimulation, RyR-mediated Ca leak produces a biphasic decay of the Ca transient with a fast early phase and a slow late phase.r Two forms of Ca leak have been studied, Ca-sensitising (induced by caffeine) and non-sensitising (induced by ryanodine) and both induce biphasic decay of the Ca transient.r Only Ca-sensitising l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
2
26
1
Order By: Relevance
“…With more extreme leak, a slow monophasic decay is seen (Sankaranarayanan et al . ). The mean data (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…With more extreme leak, a slow monophasic decay is seen (Sankaranarayanan et al . ). The mean data (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…An alternative explanation for the age‐associated decrease in k SR would be an increase in leak of Ca 2+ from the SR (Sankaranarayanan et al . ). However, protein levels of calsequestrin, RyR2 and the phosphorylation status of RyR at Ser 2808 and Ser2814 remained unchanged with age (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Future study is needed to investigate the changes of calcium transient over times. Although we did not assess the sarcoplasmic reticulum calcium content, previous studies demonstrated that the sarcoplasmic reticulum Ca 2+ content was directly proportionate to intracellular Ca 2+ transient amplitude and intracellular Ca 2+ transient decay rate [30,31].…”
Section: Discussionmentioning
confidence: 99%